1997
DOI: 10.1111/j.1474-919x.1997.tb04511.x
|View full text |Cite
|
Sign up to set email alerts
|

Brent Geese Branta bernicla and Zostera; factors affecting the exploitation of a seasonally declining food resource

Abstract: Brent Geese Branta bernicla wintering at Lindisfarne, northeastern England, fed almost exclusively on intertidal habitats. Their main food supply was two species of Eelgrass Zostera noltii and Zostera angustifolia. Although abundant when the birds arrived in September, this Zostera was rapidly depleted during the period October‐December. Brent Goose food intake rate declined with the decreasing food supply, and the birds responded by extending the time that they spent feeding. When it was no longer possible to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 10 publications
2
34
0
1
Order By: Relevance
“…) at which waterfowl leave a meadow after depleting food resources (Percival & Evans 1997, Clausen 2000. Most of the studies reporting giving-up thresholds concern brant grazing at European Zostera noltii meadows.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…) at which waterfowl leave a meadow after depleting food resources (Percival & Evans 1997, Clausen 2000. Most of the studies reporting giving-up thresholds concern brant grazing at European Zostera noltii meadows.…”
Section: Resultsmentioning
confidence: 99%
“…Many waterfowl species feed by up-ending in the water (Buchsbaum 1987, Vogel 1995, and the length of their neck-plus-head determines the maximum depth at which they can feed (Clausen 2000). In intertidal areas, birds may not be able to reach plants at high tide; feeding is often restricted to low tide when receding water makes the plants accessible (Fox 1996, Percival & Evans 1997. Observations of brant that congregate in intertidal areas have shown that the birds feed whenever they have access to seagrass, day or night, and rest when plants are inaccessible due to high water levels (Percival & Evans 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When prey is less abundant some species alter their foraging behavior (Draulans 1982, McKnight 1998), e.g. by increasing the amount of time spent foraging (Hill & Ellis 1984, Percival & Evans 1997, Crocker et al 2006, Costa 2007. Low foraging success and efficiency often result in reproductive failure (Jonsson et al 2002, Bolger et al 2005, Jodice et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, during the first period, the relationship between Brent Geese and Z. marina was tighter than between Brent Geese and Z. noltii (slopes 0.008 vs 0.004). Although the leaves of Z.marina are much larger and the calorific values of the two plants do not seem to differ (Percival and Evans 1997), not enough is known to determine if Z. marina was preferred by Brent Geese or if the relationship resulted from a lack of Z. noltii. The relative influence of the two Zostera species may in fact reflect the differences in their characteristics as food sources, in availability and in accessibility.…”
Section: Discussionmentioning
confidence: 95%